Vulvar angioleiomyoma - Stephanie Jillian Handler; Christina Truong; Tajnoos Yazdany (Wolters Kluwer Medknow Publications, 2022)
Vulvar angioleiomyoma is a very rare neoplasm. We describe the case of a 49-year-old woman who presented with a small, firm, tender labial mass. Intraoperatively, the lesion appeared hypervascular and was excised using sharp dissection. Histological and immunohistochemical analyses were necessary to make the diagnosis. The report of this extremely uncommon gynecologic lesion is important to make clinicians aware of the possibility of vulvar angioleiomyoma.